Gambaran Karakteristik Penderita Kolelitiasis di Rumah Sakit Umum Daerah Moh. Ansari Saleh Kalimantan Selatan: Description of Characteristics of Cholelitiasis Patient in Regional General Hospital Moh. Ansari Saleh South Kalimantan - Theresia Jamini; Bernedeta Trihandini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Cholelithiasis is a component of bile that accumulates, hardens and forms gallstones. The incidence of cholelithiasis is increasing every year. The incidence of cholelithiasis can be caused by various factors such as age, gender, education, weight and clinical manifestations experienced by sufferers. The purpose of this study was to describe the characteristics of cholelithiasis sufferers at Moh. Ansari Saleh, South Kalimantan. This research method uses a observational descriptive research design. The sampling technique used purposive sampling and used secondary data with a total sample of 32. Research show that the characteristics of respondents based on age were mostly 20-50 years old as many as 26 respondents (81.25%), the majority gender was female as many as 18 respondents (56.25%), the majority of respondents were overweight as many as 15 respondents (46 .87%) generally experienced upper right abdominal pain as many as 25 respondents (78.13%). It can be concluded that cholelithiasis occurs in the majority aged 20-50 years, female and overweight. In general, experience pain in the upper right abdomen, heartburn, nausea, vomiting and lack of appetite. The results of this study are expected to be a reference for underdeveloped professions to carry out health programs that refer to promotive and preventive efforts in carrying out nursing care processes in clinical settings.